Proceso atención de enfermería en paciente con diabetes mellitus tipo 2 más complicaciones de amputación. - Carrera Erazo, Linsy Ariana (2021)
The present clinical case was carried out at the IESS Babahoyo General Hospital, a patient arrives at the Emergency Department in the early hours of the morning due to a picture of general discomfort in the last two weeks, he reports presenting: intermittent fatigue, pain and numbness of the right foot, found with tachycardia, is in a feverish, oriented in time and space, saturating 98%. Patient manifests an ulcer in the lower right limb due to the presence of a cut while performing his activities as a bricklayer two weeks ago without satisfactory improvement, which after a specialist review reports that there is gas gangrene, he is referred to a surgical intervention for amputation of the same. Depression and decay in a patient after amputation surgery due to serious complications is also present in all cases of this pathology. This disease is among the top 10 causes of disability in the world, decreasing productivity and human development. Therefore, it is intended to reduce human and economic costs through early diagnosis, effective control and prevention against the development of new cases of type II diabetes as far as possible.